Pengaruh Budaya Organisasi terhadap Disiplin Kerja Karyawan PT. Wira Mas Permai di Kabupaten Banggai - Radya Pratiwi Amsir; Radia Hafid; Melizubaida Mahmud; Agil Bahsoan; Ririend Koniyo (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This research aims to determine the influence of organizational culture on employee work discipline at PT Wira Mas Permai in Banggai Regency. The research employs a quantitative method, with data processed using descriptive statistics, classical assumption tests, and hypothesis testing. The data were analyzed using simple linear regression with the assistance of IBM SPSS 21 software. The type of data used in this research is primary data, which was collected through questionnaires distributed to the employees of PT Wira Mas Permai in Banggai Regency. This research consists of a dependent variable, namely employee work discipline at PT Wira Mas Permai in Banggai Regency, and an independent variable, namely organizational culture. The results indicate that the organizational culture variable has a positive and significant influence on employee work discipline. The regression analysis indicates a positive coefficient of 0.651, which means that every increase in organizational culture will improve employee work discipline. Organizational culture contributes 42% to employee work discipline, while the remaining 58% is influenced by other factors such as leadership, motivation, and the work environment.